2004
DOI: 10.1177/000331970405500303
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Versus Nonsurveillance for Femoro-Popliteal Bypass Grafts

Abstract: This is a study of 97 patients who underwent 106 femoropopliteal bypass grafts (9 bilateral bypasses) for short-distance claudication and critical ischemia. Patients were divided into 2 groups. The first group (n=64) was followed up by use of duplex scans. The second group (n=42) was followed up in clinic without duplex surveillance. Twenty-three patients from the surveillance group developed stenoses of the grafts. Of these, 14 underwent successful angioplasty. A total of 43 grafts became blocked. Graft occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…However, because it is an exploring‐dependent test, it has several limitations, as is the case of calcified arteries or deep grafts. Despite the high sensitivity and specificity of the echo Doppler in the follow‐up of the infrainguinal vein grafts, there is conflicting information regarding the benefit in terms of cost‐effectiveness and salvation of the extremity . In addition, tracking through echo Doppler has not shown to increase the permeability of the prosthetic grafts nor of the endovascular techniques, and therefore, on the basis of the results obtained in this study and the demonstrated efficiency of the new wireless methods of clinical assistance, the establishment of a new surveillance protocol for the procedures in vascular surgery based on WSN technology could be of interest in the future.…”
Section: Discussionmentioning
confidence: 88%
“…However, because it is an exploring‐dependent test, it has several limitations, as is the case of calcified arteries or deep grafts. Despite the high sensitivity and specificity of the echo Doppler in the follow‐up of the infrainguinal vein grafts, there is conflicting information regarding the benefit in terms of cost‐effectiveness and salvation of the extremity . In addition, tracking through echo Doppler has not shown to increase the permeability of the prosthetic grafts nor of the endovascular techniques, and therefore, on the basis of the results obtained in this study and the demonstrated efficiency of the new wireless methods of clinical assistance, the establishment of a new surveillance protocol for the procedures in vascular surgery based on WSN technology could be of interest in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Por ello, no existe actualmente unanimidad en la aplicación de un programa de seguimiento estricto con eco-doppler de estos pacientes (43,66,(161)(162)(163)(164)(165) .…”
Section: Protocolos De Seguimiento En Cirugía Vascularunclassified
“…Monitoring of sites of previous surgical interventions, including sites of previous bypass surgery with either synthetic or autologous vein grafts. [11][12][13][14] 3. Monitoring of sites of various percutaneous interventions, including angioplasty, thrombolysis/ thrombectomy, atherectomy, and stent placements.…”
Section: Indications For Peripheral Arterial Examinationsmentioning
confidence: 99%